Managers' attitudes toward gene-editing technology and companies' R&D investment in gene-editing: the case of Chinese seed companies. Issue 1 (31st December 2022) - Kang, Yuwei; Deng, Haiyan; Pray, Carl; Hu, Ruifa
ABSTRACT: The Chinese government has issued a series of new policies to make it easier to industrialize gene-edited crops. However, whether technological advantages will eventually translate into industrial advantages and whether farmers will soon have access to gene-edited varieties partly depends on seed companies' willingness to produce and sell gene-edited varieties to farmers and to invest in developing their own gene-edited varieties. This study utilizes data from a survey of 111 seed companies collected in 2019 before the implementation of new regulations. This study provides empirical evidence on whether gene-edited crops will be available to farmers. The results show that the number of companies conducting research on gene-edited crops is limited, mostly to large companies. Approximately 55% of seed company managers would consider developing and selling gene-edited crops modified by SDN-1 and SDN-2 site-directed nuclease genome editing without external genetic material, whereas 46% support crops modified by SDN-3, which require gene replacement or foreign deoxyribonucleic acid (DNA) insertion and are regulated as genetically modified organisms (GMOs). The regression results show that large companies and companies with well-educated researchers are more likely to support and develop gene-editing technology. Past GM investment experience and collaboration with public institutions in gene-editing research increases the probability of company investment in gene editing R&D. These results suggest that gene-edited cultivars are more likely to be produced and sold to farmers in the future than GMOs, and that gene-edited agricultural products could have a significant market share of the seed market in the future.